2017
DOI: 10.3892/etm.2017.5133
|View full text |Cite
|
Sign up to set email alerts
|

The content of hydrogen sulfide in plasma of cirrhosis rats combined with portal hypertension and the correlation with indexes of liver function and liver fibrosis

Abstract: The purpose of this study is to investigate the content of hydrogen sulfide (H2S) in plasma of cirrhosis rats combined with portal hypertension and the correlation with indexes of liver function and liver fibrosis. Thirty female Sprague-Dawley rats were randomly divided into normal control group (NC), liver cirrhosis group (LC) and cirrhosis + propargylglycine (PPG) group (LC+PPG). Cirrhosis and portal hypertension were induced by carbon tetrachloride. Rats in LC+PPG group were intraperitoneally injected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The plasma H 2 S levels are lower in rats with liver fibrosis, and intraperitoneal injection of H 2 S synthase inhibitor propargylglycine (PPG) further promotes the fibrotic marker expression in the liver from liver cirrhosis group [85] . Both protein expressions of CSE and H 2 S content tend to be inhibited in liver fibrosis model induced by carbon tetrachloride [86] , [87] .…”
Section: Role Of H 2 S In Liver Fibrosismentioning
confidence: 99%
“…The plasma H 2 S levels are lower in rats with liver fibrosis, and intraperitoneal injection of H 2 S synthase inhibitor propargylglycine (PPG) further promotes the fibrotic marker expression in the liver from liver cirrhosis group [85] . Both protein expressions of CSE and H 2 S content tend to be inhibited in liver fibrosis model induced by carbon tetrachloride [86] , [87] .…”
Section: Role Of H 2 S In Liver Fibrosismentioning
confidence: 99%
“…In spite of current advancements in the treatment, orthotopic liver transplantation remains the only definite solution to end-stage cirrhosis [92, 94, 96]. Several studies have demonstrated that the mRNA and protein levels of hepatic CSE and the serum levels of H 2 S in rats are decreased in the cirrhosis group compared with those in the control group [18, 97, 98]. A hypothesis suggests that H 2 S may contribute to the pathogenesis of vascular dysfunction in cirrhosis [99].…”
Section: H2s In Hepatic Injurymentioning
confidence: 99%
“…The H 2 S pathway influences numerous processes throughout the body, and H 2 S has thus begun to be considered for the treatment of various disorders, particularly those affecting the cardiovascular, gastrointestinal and respiratory systems and CNS (Wei et al ., 2017; Das et al ., 2018). Traditionally, two different approaches for modulating H 2 S levels have been used: enhancing H 2 S levels, through increased production or bioavailability for instance, and decreasing H 2 S levels, through inhibition of the enzymes responsible for H 2 S synthesis, for example (Li et al ., 2008; Caliendo et al ., 2010).…”
Section: Targeting the H2s Pathway In The Prevention And Treatment Ofmentioning
confidence: 99%